What is the significance of free digital goods on economic welfare - Fjölnir Þrastarson 1996-; Friðrik Örn Gunnarsson 1996- (2020)
The divergence between economic growth and welfare is increasing. The non-market aspect of free digital goods results in a key driver of welfare remaining unaccounted for by current economic measurements despite replacing traditional goods synonymous with our everyday life. This study aims to discover the impact free digital goods have on the economic welfare of Icelandic people by asking for their required monetary amount to give up access to a service. Research on this topic has been performed in different parts of the world, but not in Iceland. Answers were gathered in a survey from Icelandic internet users through convenience and snowball sampling. We employed a combined dichotomous choice and open-ended question format for each bundle of goods. Our conclusion is that free digital goods contribute significantly to the economic welfare of Icelandic people. We find that the median participant required a compensation of more than 35% of their salary to give up access to all the services we associate with free digital goods. Specifically, services associated with work were higher valued. Compared with other studies, we found that our participants valued messaging and social media more than their US counterparts suggesting a difference in consumer behavior between the countries. The results of our study confirm that the value derived from free digital goods are significantly higher than current economic measurements suggest. Further studies on the topic are necessary to guide future policy decisions.